Analysis of self-trapped hole mobility in alkali halides and metal halides - Popov, Anatoli I.; Kotomin, Eugene A.; Maier, Joachim (Elsevier B.V., 2017)
The small radius hole polarons (self-trapped holes (STH) known also as the Vk centers) are very common color centers observed in numerous alkali halides and alkaline-earth halides. Their mobility controls the rate of secondary reactions between electron and hole defects and thus radiation stability/sensitivity of materials. We have analysed here the correlation between the temperatures at which hole polarons start migration in a series of alkali halides (fluorites, chlorides, bromides, iodides) and the lattice displacement around quasi-molecule. These results are especially important for identification of the self-trapped holes, for example, in novel scintillating materials such as SrI2, as well as in a large family of perovskite halides and more complex halide materials.
Support from Latvian National Research Program IMIS2 (2014–2017) and LZP Grant No. 237/2012 (2013–2016) is greatly appreciated.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics